Coexistence of five extrinsic accessory flexor muscles collectively able to flex all five digits of the hand - Ethan L. Snow; Andrew C. White; Alexis M. Tyce; Travis L. McCumber (Elsevier, 2022)
Introduction: Anatomical variations in antebrachial (forearm) musculature are relatively common. While most are asymptomatic, some can develop serious sequelae. Accessory forearm muscles can cause anterior interosseous nerve syndrome (AINS) and pronator syndrome, auxiliary muscle attachments can cause symptomatic supernumerary muscle belly (SSMB) syndrome, and extra tendon structures in the carpal tunnel can cause carpal tunnel syndrome (CTS) and tendinopathy. Many investigators have studied accessory muscles to the flexor pollicis longus (a-FPL) and flexor digitorum profundus (a-FDP), but few have examined their coexistence, and no one has reported a single case with resulting ability to flex all five digits. The objectives of this study is to analyze a previously undocumented and remarkably unique case of one a-FPL coexisting with four a-FDP muscles collectively able to flex all five digits of the hand and discuss the relevant clinical implications. Materials and methods: One a-FPL and four a-FDPs were discovered on one right forearm during routine cadaver dissection. All neurovascular and musculoskeletal components within the flexor compartment, carpal tunnel, and palm were carefully cleaned of extraneous fascia. Contiguous muscles were reflected to view the muscle bellies, tendons, and proximal and distal attachments of the a-FPL and a-FDP muscles. The a-FPL and a-FDPs were measured and photographed in situ, and maximal isometric force (Fmax) was calculated for each muscle. The FPL and FDP were also analyzed to gauge accessory muscle impact. Histological analysis examined an intertendinous structure that formed from the accessory tendons in the carpal tunnel, and the non-typical morphologies were discussed regarding their clinical implications. Results: A bicipital a-FDP with radial (a-FDPr) and ulnar (a-FDPu) heads was discovered adjacent and medial to an a-FPL. The a-FPL and bicipital a-FDP originated separately from the coronoid process of the ulna and were innervated by the anterior interosseous nerve. The a-FDPr flexed digits #3 and #4, and a-FDPu flexed digits #4 and #5. The a-FPL was especially unique: part of its tendon merged with the proximal third of FPL (to flex digit #1) while the remainder continued distal, drawing two additional distinct accessory muscle bellies from FPL (a-FDPFPL) and FDP (a-FDPFDP). The common tendon of a-FPL, FPL, a-FDPFPL, and a-FDPFDP distributed the adjoined forces to flex digits #2, #3, and #4 via an intertendinous structure in the carpal tunnel. The Fmax for a-FPL, a-FDPr, a-FDPu, a-FDPFPL, and a-FDPFDP was 4.55 N, 1.22 N, 0.98 N, 3.44 N, and 0.58 N respectively. Histological analysis of the intertendinous structure revealed evidence of angiogenesis, increased cellularity, and disorganized extracellular stroma. Conclusions: The present study investigates an in-depth analysis of five coexisting extrinsic accessory flexor muscles with the collective ability to flex all five digits of the hand. AINS, pronator syndrome, CTS, SSMB syndrome, and tendinopathy are conferred as likely clinical implications of the non-typical muscle morphologies that could cause significant issues with prehension, distal pinch, and digit independence. This report may serve as an important resource for orthopedic surgeons, occupational and physical therapy providers, and medical educators when presented with a similar clinical or educational case.